A tandem death effector domain-containing protein inhibits the IMD signaling pathway via forming amyloid-like aggregates with the caspase-8 homolog DREDD. (November 2019) - Hu, Jie; Wang, Xinyi; Xiao, Xiaoyi; Sun, Chang; Xia, Qingyou; Wang, Fei
Abstract: Negative regulation of the immune signaling pathway involves diverse negative regulators that target different signaling molecules. One of the signaling molecules, DREDD, which activates the NF-κB transcription factor Relish in the IMD pathway, is a homolog of mammalian caspase-8. Some structural related proteins have been identified to regulate the activity of caspase-8 in signaling complex assembly. However, it is unknown in insects whether the IMD pathway undergoes such a down-regulation. In this study, we explored the regulatory role of a newly identified protein BmCaspase-8 like (BmCasp8L) in silkworm, which displays high sequence similarity with the N-terminus of BmDREDD to the IMD pathway, and investigated its mechanism. Domain prediction, phylogenic analysis and gene architecture suggests BmCasp8L acts as a potential inhibitor to BmDREDD. We then found it is highly expressed in the fat body and hemocytes, and suppresses the cleavage of BmRelish and BmIMD mediated by BmDREDD upon PGN stimulation, resulting in deficiency in antimicrobial peptides production. Besides the inhibitory role in the IMD pathway, it also suppresses the BmDREDD-induced apoptosis. By investigating the amyloidal activity of BmCasp8L and its interaction with BmDREDD and BmFADD, we demonstrated that BmCasp8L forms amyloid-like aggregates in vitro as well as in vivo, and it inactivates BmDREDD by blending into the amyloidal speck-like structure formed by BmDREDD and BmFADD that is required for BmDREDD activity. Taken together, our results demonstrate BmCasp8L inhibits the IMD signaling pathway via forming amyloidal aggregates with BmDREDD, suggesting an evolutionarily conserved regulatory mechanism of innate immune signaling pathway. Graphical abstract: Image 1 Highlights: Divergence in  dredd  gene architecture suggests BmCasp8L may function similar to caspase domain-lacking isoforms of DREDD. BmCasp8L suppresses the cleavage of both BmIMD and BmRelish, resulting in deficiency in antimicrobial peptides production. BmCasp8L forms amyloid aggregates in vitro as well as in vivo. BmCasp8L is comingled into the signaling complex formed by BmDREDD and BmFADD via interaction with both of them.